2018
DOI: 10.1111/acps.12862
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine for major mental disorders: a systematic review and meta‐analysis of randomized controlled trials

Abstract: Adjunctive NAC appears to be a safe treatment that has efficacy for schizophrenia, but not for bipolar disorder or MDD. Further higher quality RCTs are warranted to determine the role of adjunctive NAC in the treatment of major psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 54 publications
1
51
0
Order By: Relevance
“…Across all the above disorders, the rates of discontinuation and severe adverse events from N‐acetylcysteine supplementation did not differ significantly from the placebo conditions. There was no significant difference in rates of mild adverse events (particularly with regards to gastrointestinal upset) in people with schizophrenia (N=186, n=2, OR=1.56, 95% CI: 0.87‐2.80, p=0.14, I 2 =0), but N‐acetylcysteine supplementation was associated with higher rates of mild adverse events in mood disorders (N=574, n=5, OR=1.61, 95% CI: 1.01‐2.59, p=0.049).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Across all the above disorders, the rates of discontinuation and severe adverse events from N‐acetylcysteine supplementation did not differ significantly from the placebo conditions. There was no significant difference in rates of mild adverse events (particularly with regards to gastrointestinal upset) in people with schizophrenia (N=186, n=2, OR=1.56, 95% CI: 0.87‐2.80, p=0.14, I 2 =0), but N‐acetylcysteine supplementation was associated with higher rates of mild adverse events in mood disorders (N=574, n=5, OR=1.61, 95% CI: 1.01‐2.59, p=0.049).…”
Section: Resultsmentioning
confidence: 94%
“…As an adjunctive treatment for individuals with bipolar disorder (N=224, n=2), 2 g/day N‐acetylcysteine did not differ from placebo in its impact on overall illness severity (Clinical Global Impression ‐ Severity, CGI‐S: SMD=0.11, 95% CI: –0.15 to 0.37, p=0.42, I 2 =90%, and Clinical Global Impression ‐ Improvement, CGI‐I: SMD=0.16, 95% CI: –0.09 to 0.42, p=0.22, I 2 =0%) or mania ratings (N=224, n=2, SMD=0.05, 95% CI: –0.2 to 0.31, p=0.68, I 2 =0.01%). N‐acetylcysteine was also found to be ineffective on depressive symptoms in people with bipolar disorder (N=124, n=2, SMD=0.59, 95% CI: –0.3 to 1.48, p=0.19, I 2 =83%).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, a recent RCT demonstrated continuous effects of adjunctive NAC approach in long‐term treatment and effects in early psychosis . A recent meta‐analysis from 6 RCT showed that adjunctive NAC appears to have efficacy for schizophrenia …”
Section: Treatment Based On Glutamate Hypothesismentioning
confidence: 99%